2020
DOI: 10.1007/s00190-020-01355-x
|View full text |Cite
|
Sign up to set email alerts
|

Radial interpolation of GPS and leveling data of ground deformation in a resurgent caldera: application to Campi Flegrei (Italy)

Abstract: This study presents a new method, called the Radial Interpolation Method, to interpolate data characterized by an approximately radial pattern around a relatively constrained central zone, such as the ground deformation patterns shown in many active volcanic areas. The method enables the fast production of short-term deformation maps on the base of spatially sparse ground deformation measurements and can provide uncertainty quantification on the interpolated values, fundamental for hazard assessment purposes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 113 publications
2
22
0
Order By: Relevance
“…Recent structural studies in the Campi Flegrei caldera, both inland (Isaia, Vitale, Di Giuseppe, et al., 2015; Vitale & Isaia, 2014; Vitale et al., 2019) and offshore (e.g., Natale et al., 2020), have shown that faults are located close to volcanic vents and caldera rims. These structures are associated with both eruptive and ground deformation activity (e.g., Bevilacqua, Neri, De Martino, et al., 2020). Generally, these structures show a prevalence of regional tectonic directions (NW‐SE and NE‐SW); however, NNE‐SSW‐ and WNW‐ESE trending faults are associated with the youngest deformational episodes within the caldera (e.g., Vitale & Isaia, 2014; Vitale et al., 2019).…”
Section: Geological Setting Of the Campi Flegrei Calderamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent structural studies in the Campi Flegrei caldera, both inland (Isaia, Vitale, Di Giuseppe, et al., 2015; Vitale & Isaia, 2014; Vitale et al., 2019) and offshore (e.g., Natale et al., 2020), have shown that faults are located close to volcanic vents and caldera rims. These structures are associated with both eruptive and ground deformation activity (e.g., Bevilacqua, Neri, De Martino, et al., 2020). Generally, these structures show a prevalence of regional tectonic directions (NW‐SE and NE‐SW); however, NNE‐SSW‐ and WNW‐ESE trending faults are associated with the youngest deformational episodes within the caldera (e.g., Vitale & Isaia, 2014; Vitale et al., 2019).…”
Section: Geological Setting Of the Campi Flegrei Calderamentioning
confidence: 99%
“…According to Vitale and Isaia (2014), the fault orientation is the result of the interplay between the regional tectonic field associated with the opening of the Tyrrhenian Sea (Vitale & Ciarcia, 2013) and the local volcano‐tectonic deformation. The central sector is also characterized by intense degassing and hydrothermal activity (e.g., Cardellini et al., 2017; Chiodini, Caliro, et al., 2012) and by the highest values of surface fractures and fault density, particularly around the town of Pozzuoli and in the Solfatara area (Bevilacqua, Isaia, et al., 2015; Bevilacqua, Neri, De Martino, et al., 2020).…”
Section: Geological Setting Of the Campi Flegrei Calderamentioning
confidence: 99%
“…In Figure 5 the present continuous geodetic network (GPS and Tiltmeters) at CFc is superposed to the bell-shaped uplift centred on the caldera (a) and to the long-term probability map of vent opening (b; Selva et al, 2012;Bevilacqua et al, 2015;Bevilacqua et al, 2020). The present spatial distribution of GPS stations is satisfactory to test the invariance of the bell-shaped deformation pattern.…”
Section: Implications For Operational Monitoring Of Campi Flegrei Cal...mentioning
confidence: 72%
“…The recent history of CFc therefore demonstrates a restless behaviour resulting from magma accumulation, without necessarily producing eruptions. Volcanic centres from the last 15 ka show an inward migrating pattern inside the caldera and the probability of opening of a new vent is the highest along the on-land periphery of the resurgent area (Selva et al, 2012;Rivalta et al, 2019;Bevilacqua et al, 2020).…”
Section: A Reference Model For Campi Flegrei Calderamentioning
confidence: 99%
“…The most relevant signs that the hydrothermally active Campi Flegrei volcanic field (CF; Fig. 1 a) is reawakening are, for example, the intense increases in surface uplift 1 , degassing 2 , and seismicity 3 , 4 . The hydrothermal area of Pisciarelli (Fig.…”
Section: Introductionmentioning
confidence: 99%